DIFFERENT LEVELS OF COMMUNICATION ACTIVITIES IN SPEAKING EXERCISES OF BSE ENGLISH TEXTBOOK - Kurnihayati Kurnihayati (EJI (English Journal of Indragiri) : Studies in Education, Literature, and Linguistics, 2018)
The use of a textbook is a crucial one, since a textbook plays an important role in learning activities, a textbook can be a source of the lesson. And evaluating a textbook should be applied as a way to keep the usefulness of the textbook. So, this study has an aim to evaluate the speaking exercises in curriculum 2013 textbook. The concern of this study is the different levels of communication activities in the textbook that mentioned by Littlewood (2004). According to Littlewood, there are five different levels of communicative activities; those are non-communicative, pre-communicative, communicative, structured communication and authentic communication. In gathering the data, it was used checklists from Littlewood (2004) to analyze fifteen speaking exercises from the textbook. After analyzing the exercises, it is found that communicative level which has good level. The results of this study is one speaking exercise is non-communicative, two speaking exercises for each pre-communicative, communicative and structured communication. And eight speaking exercises in this textbook are in authentic communication level. The findings of this study can be used as the inputs for the consideration in using this textbook.